Reflections to Advance the Collaborative Production of Knowledge and Protection of Archaeological Heritage in Uruguay. Issue 3 (August 2022) - Suárez, Rafael; Malán, Maira; Vallvé, Elena
Abstract: In Uruguay, there are records of archaeological collections at least since Darwin's visit in 1832. Since then, the role of collections and collectors has been changing in relation to official institutions, researchers, and professional archaeologists. In the years following the creation of the university degree in anthropology, during the 1980s and 1990s, academic and official speeches considered collectors one of the greatest threats to the development of the discipline in the country. Their collections were seen as useless for research, and it was argued that they had no context. New generations of archaeologists have been reversing this situation, redefining the research of archaeological collections and reviewing the relationships and interactions with nonacademic stakeholders. We present some of our experiences here, based on students' training in this line of work, the integration of responsible and responsive collectors in the research process and site conservation, the collaborative register of archaeological sites, and the promotion of donation or conservation of collections (avoiding commercialization). We propose possible work methodologies at the national level, such as the formation of research groups, which involve the coparticipation of different stakeholders, the development of a professional code of ethics, and changes in legislation.